Participação de idosos e idosas no mercado de trabalho no contexto da divisão sexual do trabalho - Kurz, Marcio Rogério (2014)
A striking aspecto of modern societies is the sharp growth forecast for the elderly population in all countries, especially in developing countries. For the year 2050, official indicators point to 2 billion older people around the world, and therefore there is a need to stimulate the social studies of the elderly, especially in the contexto of Brazil. Changes in age structure may cause social, economic and environmental implications, whose investigation Will point paths and proposals for action in Brazil the official institute’s projections point to 35 million elderly in 2050. Age can affect the contribution to the work, both the permanence of the Elder in his position, being productive, as your return after retirement. The capacity and willingness of older workers become active as long as possible depend on your health status and working conditions proposed in this social group. This quantitative study, based on the descriptive statistics, seeks to analyze the integration of elderly in the international and Brazilian labor market, identifying the main legal nature and occupations, and analyzes the participation of older people in the formal labor market in the city of Curitiba at different levels of education. The international data are from the International Labour Organisation (ILO) and the Brazilian numbers are from the Ministry of Labour and Employment (MTE). The main international results indicate approximately 85 million elderly in the global labor market, and nearly 1.6 million unemployed older people. The main Brazilian results indicate that, both in the city of Curitiba as nationwide, elderly men predominate in almost all areas analyzed and in almost all salary ranges. Older women are concentrated in lower-paid groups, with up to a monthly minimum wage.